Reliability and validity study of the Spanish adaptation of the "Educational Practices Questionnaire" (EPQ). - Mariona Farrés-Tarafa; Juan Roldán-Merino; Urbano Lorenzo-Seva; Barbara Hurtado-Pardos; Ainoa Biurrun-Garrido; Lorena Molina-Raya; Maria-Jose Morera-Pomarede; David Bande; Marta Raurell-Torredà; Irma Casas (PLoS ONE, 2020)
The Educational Practices Questionnaire is an instrument for assessing students perceptions of best educational practices in simulation. As for other countries, in Spain, it is necessary to have validated rubrics to measure the effects of simulation. The objective of this study was to carry out a translation and cultural adaptation of the Educational Practices Questionnaire into Spanish and analyze its reliability and validity. The study was carried out in two phases: (1) adaptation of the questionnaire into Spanish. (2) Cross-sectional study in a sample of 626 nursing students. Psychometric properties were analyzed in terms of reliability and construct validity by confirmatory and exploratory factor analysis. The exploratory and confirmatory factor analyses showed that the one-dimensional model is acceptable for both scales (presence and importance). The results show that the participants' scores can be calculated and interpreted for the general factor and also for the four subscales. Cronbach's alpha and the Omega Index were also suitable for all the scales and for each of the dimensions. The Educational Practices Questionnaire is a simple and easy-to-administer tool to measure how nursing degree students perceive the presence and importance of best educational practices.